Same-spot micro-ECM based on constant-accelerated movement of the electrode - Chen, Shun-Tong; Chiu, Wei-Jen; Chiu, Chi-Hsien (Materials and manufacturing processes, 2024)
An injector nozzle needs a precision upside-down tapered-microhole, and the nozzle material is often a high temperature corrosion resistant alloy that is very difficult to machine. In this study, a same-spot micro-ECM technique with the electrode in "constant-accelerated movement" was proposed. Insulated by electrophoretic deposition, an ultra-fine electrode was inserted deep into the hole and subject gradually to withdrawal from the hole at constant rpm and acceleration. The electric flux intensity acting on the hole-wall gradually decreased and so did the material dissolution rate on the hole-wall, thus creating an upside-down tapered hole with the desired taper-rate. The experiments' results showed that upside-down tapered holes with taper-rates of T(a=1) = 0.094 (Ra 0.593 μm) and T(a = 2) = 0.02 (Ra 0.435 μm) were produced when the electrode was subject to constant-acceleration withdrawal at 1.0 and 2.0 μm/s2, respectively, and respective spray angles of 31° and 23° were created. The proposed technique is commercially promising in industry.